World history 50 things you really need to know - Crofton, Ian (Quercus, 2011)
People often complain that in history lessons at school they were taught just a few topics - the Romans, the Tudors, the Nazis - and how they have no idea at all about what happened in between. To remedy this, World History: 50 Key Milestones You Really Need to Know offers brief and stimulating outlines of key developments in the history of the world, from the beginning of agriculture 10,000 years ago to the attack on the Twin Towers on 9/11. Ian Crofton, the author of several books of popular history including The Kings and Queens of England, Traitors and Turncoats and History Without the Boring Bits, brings his lively style to bear in a series of essays ranging from ancient Egypt to modern China, from the Vikings and the Mongols to the French Revolution and the Cold War. Each essay is accompanied by a detailed time line of dates and events, and the flavour of the period concerned is brought to life by selected contemporary quotations from figures as diverse as Aristotle, Ashoka, Saladin, Christopher Columbus, Martin Luther, Suleiman the Magnificent, Galileo, Voltaire, Thomas Jefferson, Mary Wollstonecraft, Napoleon, Lincoln, Lenin and Winston Churchill. In addition, box features throw light on a range of related topics, from the Nazca Lines to Renaissance man, from Confucianism and the state to Alexander the Great's horse, from Islamic science and the Barbary corsairs to the Enigma code and the atomic bomb.